2019
DOI: 10.4153/s0008414x19000397
|View full text |Cite
|
Sign up to set email alerts
|

On the Combinatorics of Gentle Algebras

Abstract: For A a gentle algebra, and X and Y string modules, we construct a combinatorial basis for Hom(X, τ Y ). We use this to describe support τ -tilting modules for A. We give a combinatorial realization of maps in both directions realizing the bijection between support τ -tilting modules and functorially finite torsion classes. We give an explicit basis of Ext 1 (Y, X) as short exact sequences. We analyze several constructions given in a more restricted, combinatorial setting by McConville [McC], showing that many… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…REMARK 8.13. While this manuscript was under review, several authors have studied the combinatorial aspects of the representation theory of gentle algebras; for instance, see [4,2,31,32]. In [2,31], it is shown that all gentle algebras can be realized as tiling algebras associated with unpunctured surfaces.…”
Section: Simple-minded Collectionsmentioning
confidence: 99%
“…REMARK 8.13. While this manuscript was under review, several authors have studied the combinatorial aspects of the representation theory of gentle algebras; for instance, see [4,2,31,32]. In [2,31], it is shown that all gentle algebras can be realized as tiling algebras associated with unpunctured surfaces.…”
Section: Simple-minded Collectionsmentioning
confidence: 99%
“…We note that a basis for extensions between string modules over gentle algebras is also given, by different techniques, in [6] building on the work in [19].…”
mentioning
confidence: 99%
“…Gentle algebras are Gorenstein [24], closed under tilting and derived equivalence [38,39], and they are ubiquitous, for instance they occur in contexts such as Fukaya categories [27], dimer models [8], enveloping algebras of Lie algebras [29] and cluster theory. As such, there has been widespread interest in this class of algebras; see for example [10,14,15,37] for recent developments in this area.…”
Section: Introductionmentioning
confidence: 99%
“…10. A tiling algebra A P is of finite representation type if and only if every permissible simple closed curve c is such that |I P (c)| 1.…”
mentioning
confidence: 99%